2021
DOI: 10.1146/annurev-immunol-093019-111748
|View full text |Cite
|
Sign up to set email alerts
|

Origins, Biology, and Diseases of Tissue Macrophages

Abstract: Tissue-resident macrophages are present in most tissues with developmental, self-renewal, or functional attributes that do not easily fit into a textbook picture of a plastic and multifunctional macrophage originating from hematopoietic stem cells; nor does it fit a pro- versus anti-inflammatory paradigm. This review presents and discusses current knowledge on the developmental biology of macrophages from an evolutionary perspective focused on the function of macrophages, which may aid in study of developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 274 publications
5
96
0
Order By: Relevance
“…98 The importance of a "competent" cell state that allows for specific polarization highlights the role of ontogeny and epigenetic influences on macrophage identity. 96 Environmental signals drive the selection of specific enhancers, adding another layer of complexity to the regulation of tissue-resident macrophage identity. 102,103 Indeed, a study comparing the enhancer landscapes of microglia and large peritoneal macrophages revealed that 60% of the active enhancers are shared, but 40% are macrophage subset-specific.…”
Section: Determinants Of Cellular Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…98 The importance of a "competent" cell state that allows for specific polarization highlights the role of ontogeny and epigenetic influences on macrophage identity. 96 Environmental signals drive the selection of specific enhancers, adding another layer of complexity to the regulation of tissue-resident macrophage identity. 102,103 Indeed, a study comparing the enhancer landscapes of microglia and large peritoneal macrophages revealed that 60% of the active enhancers are shared, but 40% are macrophage subset-specific.…”
Section: Determinants Of Cellular Functionmentioning
confidence: 99%
“…Many of the transcription factors that are important for the programming of macrophage populations have been identified. 96 These include core transcription factors that are common to all macrophage populations and play a role in macrophage differentiation, such as PU.1, MYB, C-MAF, MAFB, and ZEB2, as well as tissue-specific transcription factors such as BACH1 and SPIC for red pulp macrophages 72,97 and GATA6 for peritoneal macrophages. 94,98,99 A few known examples of environmental signals that drive expression of these transcription factors and polarization of tissue-resident macrophage populations include retinoic acid for cavity macrophages 98,100 and heme and IL-33 for red pulp macrophages.…”
Section: Determinants Of Cellular Functionmentioning
confidence: 99%
“…We show that actomyosin contractility is non-critical for sampling macrophage populations, as they can survey their surrounding by two equally efficient strategies: (a) migration-based surveillance by contractile, low-protrusive cells, or (b) protrusion-based surveillance by less contractile, lowmigrating cells. We speculate that both surveillance modes are likely reflected in the heterogeneity of resident macrophages in mammalian tissues (Bleriot et al, 2020;Cox et al, 2021), contributing to the robustness of macrophage network function. Although we know that macrophages of different developmental origin co-exist in many tissues (Bleriot et al, 2020;Cox et al, 2021), we have only limited understanding about their cytoskeletal properties.…”
Section: Discussionmentioning
confidence: 97%
“…We speculate that both surveillance modes are likely reflected in the heterogeneity of resident macrophages in mammalian tissues (Bleriot et al, 2020;Cox et al, 2021), contributing to the robustness of macrophage network function. Although we know that macrophages of different developmental origin co-exist in many tissues (Bleriot et al, 2020;Cox et al, 2021), we have only limited understanding about their cytoskeletal properties. In future studies it will be interesting to address how distinct macrophage subsets differ in their protrusive and contractile forces and how these factors determine the surveillance potential and adaptation of macrophages to a specific tissue compartment (Okabe & Medzhitov, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation